Iron starvation results in up-regulation of a probable Haloferax volcanii siderophore transporter - Sailer, Anna-Lena; Jevtic, Zivojin; Stoll, Britta; Wörtz, Julia; Sharma, Kundan; Urlaub, Henning; Dyall-Smith, Mike; Pfeiffer, Friedhelm; Marchfelder, Anita; Lenz, Christof (Frontiers in Microbiology, 2024)
The response of the haloarchaeal model organism Haloferax volcanii to iron starvation was analysed at the proteome level by data-independent acquisition mass spectrometry. Cells grown in minimal medium with normal iron levels were compared to those grown under low iron conditions, with samples being separated into membrane and cytoplasmic fractions in order to focus on import/export processes which are frequently associated with metal homeostasis. Iron starvation not only caused a severe retardation of growth but also altered the levels of many proteins. Using a comprehensive annotated spectral library and data-independent acquisition mass spectrometry (DIA-MS), we found that iron starvation resulted in significant changes to both the membrane and the soluble proteomes of Hfx. volcanii. The most affected protein is the RND family permease HVO_A0467, which is 44fold enriched in cells grown under iron starvation. The gene HVO_A0467 can be deleted suggesting that it is not essential under standard conditions. Compared to wild type cells the deletion strain shows only slight changes in growth and cell morphologies show no differences. Molecular docking predictions indicated that HVO_A0467 may be an exporter of the siderophore schizokinen for which a potential biosynthesis cluster is encoded in the Hfx. volcanii genome. Together, these findings confirm the importance of iron for archaeal cells and suggest HVO_0467 as a siderophore exporter.